Investigating the effectiveness of solution-oriented narrative therapy on boredom, engagement and hope of women applying for divorce in Shahrekord city - Taheri Fard, Ahmad; Javdan, Moosa; Samavi, Seyed Abdulwahab; Najarpourian, Samaneh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of investigating the effectiveness of solution-oriented narrative therapy on boredom, passion and hope of women seeking divorce. Methods: This study was conducted with a quasi-experimental design with a pre-test-post-test design with a control group along with a follow-up test in Shahrekord city. The statistical population of this research included women seeking divorce in Shahrekord city. The research sample includes 24 people who were selected by purposive sampling method and were randomly divided into two experimental groups (12 people) and control (12 people) and according to Pines' marital despondency questionnaire (1996), Singer and Labanko's marital desire questionnaire Messer, Bodley (2015) and the hope scale of Snyder, Harris, Anderson, Holleran, Ironic and Simon (1991), answered in the pre-test, post-test and follow-up test. The participants in the experiment underwent eight ninety-minute sessions of solution-oriented narrative therapy according to the treatment protocol of Linda Matt Calf (2016), and the control group did not receive any intervention. Results: The results showed that solution-oriented narrative therapy can reduce boredom (F=65.93, P